UPAYA MENINGKATKAN KECERDASAN KOGNITIF ANAK USIA DINI MELALUI PEMBELAJARAN BERBASIS KOMPUTER PADA KELOMPOK B DI TK AZ ZAITUN BEKASI - Nina Yuminar Priyanti (Universitas Islam Lamongan, 2020)
The purpose of this study was to determined the increase of early childhood cognitive intelligence through computer-based learning in group B through paint media. This study used a classroom action research model with two cycles. Each cycle consisting of four stages, there was planning, implementing the action, observing, and reflecting. The subject of this study was group B with a total of 15 children consisting of 7 boys and 8 girls.Â In this study, pre-cycle used before computer learning was carried out, children's cognitive abilities showed a low value, that was 32%. However, after taking action in cycle I the percentage of children increased by about 61% and cycle II had an increase, showing that 89% of children were able to distinguish geometric shapes.Â Computer-based learning through Paint media can be used as an interesting and fun medium to improve early childhood cognitive. so it can stimulate children's development and develop children's thinking skills.